# If #Log_y6=x#, #Log_y3.5=z# and #6a=3.5# then #a=??#

##
If #Log_y6=x# , #Log_y3.5=z# and #6a=3.5# then #a=??#

#(a)# #xz#

#(b)# #z/x#

#(c)# #z+x#

#(d)# #z-x#

I searched on internet about correct answer and it was #(b)# #z/x# , but I don't know why #(b)# is correct. I think that all the answers listed are incorrect.

If

I searched on internet about correct answer and it was

##### 1 Answer

Feb 15, 2018

I got

#### Explanation:

We're told that

We can rearrange these equations to put them into exponential form:

And substitute in the values: